THE SOCIAL MATTER OF INCLUDING PUPILS WITH SPECIAL EDUCATIONAL NEEDS IN PHYSICAL EDUCATION CLASSES - Alexandru Marius MEZO; Bogdan ALMAJAN-GUȚĂ; Simona PETRACOVSCHI (Cluj University Press, 2022)
Introduction: The specific educational needs of pre-university teachers in physical education and sports classes in working with students with special educational needs has certain peculiarities. Objectives: Identifying the profile of the physical education and sports teacher; their attitudes, skills and abilities necessary to promote the social inclusion of students with special educational needs in the physical education and sports classes provided in the school curriculum. Identifying examples of good practice to combat the social exclusion of students with special educational needs in physical education and sports classes. Materials and methods: Using the Systematic Review method, a number of 434 articles were initially identified. Following the establishment of the inclusion and exclusion criteria, a number of 18 studies were retained for analysis. Results: Peer guidance has proven to be an effective way to facilitate inclusive physical education. However, supplementing the findings with qualitative data from students with disabilities and their teachers on the peer guidance strategy in different cultural and school settings could provide a deeper and more comprehensive understanding of the strategy. Furthermore, it is also suggested that more studies could focus on the roles and responsibilities of support teachers in physical education and sports classes. Conclusions: Future studies examining the effects of inclusion on students with or without disabilities should also address student attitudes, social interactions, and the acquisition of cognitive development and motor skills in inclusive physical education settings. Received 2022 April 20; Revised 2022 June 02; Accepted 2022 June 8; Available online 2022 June 30; Available print 2022 August 30. REZUMAT. Problematica socială a incluziunii elevilor cu cerințe educaționale speciale în cadrul lecțiilor de educație fizică și sport - O analiză sistematică a literaturii de specialitate. Introducere: Nevoile educaționale specifice ale cadrelor didactice din învățământul preuniversitar în cadrul orelor de educație fizică și sport în lucrul cu elevii cu cerințe educaționale speciale are anumite particularități. Obiective: Identificarea profilului cadrului didactic de educație fizică și sport; a atitudinilor, a competențelor și abilităților acestora necesare promovării includerii sociale a elevilor cu cerințe educaționale speciale în cadrul orelor de educație fizică și sport prevăzute în programa școlară. Identificarea de exemple de bune practici în vederea combaterii excluziunii sociale a elevilor cu cerințe educaționale speciale în cadrul orelor de educație fizică și sport. Materiale și metode: utilizând metoda Systematic Review, au fost identificate inițial un număr de 434 articole. În urma stabilirii criteriilor de includere și excludere au fost reținute pentru analiză un număr de 18 studii. Rezultate: Îndrumarea de la egal la egal s-a dovedit a fi o metodă eficientă de facilitare a educației fizice incluzive. Cu toate acestea, completarea constatărilor cu date calitative de la elevii cu dizabilități și profesorii lor cu privire la strategia de îndrumare de la egal la egal în diferite setări culturale și școlare ar putea oferi o înțelegere mai profundă și mai cuprinzătoare a strategiei. Mai mult, se sugerează, de asemenea, că mai multe studii s-ar putea concentra pe rolurile și responsabilitățile profesorilor de sprijin în cadrul orelor de educație fizică și sport. Concluzii: Studiile viitoare care examinează efectele incluziunii asupra elevilor cu sau fără dizabilități trebuie de asemenea să abordeze atitudinile elevilor, interacțiunile sociale și dobândirea dezvoltării cognitive și a abilităților motorii în medii incluzive de educație fizică. Cuvinte cheie: problematica socială (formarea continuă), incluziune, educație incluzivă, nevoi speciale, educație fizică și sport (cadre didactice)